2018
DOI: 10.1021/acs.energyfuels.7b03310
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Catalytic Effect of Circulating Ash on the Primary Volatiles from Slow and Fast Pyrolysis of Coal

Abstract: The lab-scale fixed-bed pyrolyzer by circulating ash as heat carrier was used to study the secondary catalytic effect of circulating ash on the primary volatiles from slow and fast pyrolysis of coal. Different mass ratios of ash to coal were layered in the pyrolyzer. Combined with the simulated distillation analysis, gas chromatograph-mass spectrum (GC-MS), and elemental analysis, the yields and compositions of gas, tar, and semicoke were analyzed. The results show that circulating ash catalyzes the cracking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 32 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The smart phone controls the rheometer through Bluetooth interface. It has been confirmed that the behavior of fresh concrete is similar to Bingham fluid (Equation ( 1)), where τ (Pa) is the shear stress, τ 0 (Pa) is the yield stress, and η (Pa•s) is the plastic viscosity [38][39][40][41]. The corresponding relationship can be expressed by Equation (2), where g (Nm) and H (Ns) are flow resistance and torque viscosity respectively, which are called relative yield stress and relative plastic viscosity [42,43].…”
Section: Measurement Of Rheological Properties Of Wet Shotcretementioning
confidence: 76%
“…The smart phone controls the rheometer through Bluetooth interface. It has been confirmed that the behavior of fresh concrete is similar to Bingham fluid (Equation ( 1)), where τ (Pa) is the shear stress, τ 0 (Pa) is the yield stress, and η (Pa•s) is the plastic viscosity [38][39][40][41]. The corresponding relationship can be expressed by Equation (2), where g (Nm) and H (Ns) are flow resistance and torque viscosity respectively, which are called relative yield stress and relative plastic viscosity [42,43].…”
Section: Measurement Of Rheological Properties Of Wet Shotcretementioning
confidence: 76%
“…First, according to the FTIR analyses, more phenolic hydroxyl groups were generated in treated coal samples. Second, the removal of water-soluble organic metals inhibited the conversion of macromolecular phenolic compounds to small molecules. More phenolic compounds were produced in tar samples. Correspondingly, the relative content of monocyclic aromatic hydrocarbons decreased.…”
Section: Resultsmentioning
confidence: 99%